Destination Management Organization (DMO) Policy Analysis of Sustainable Tourism in the 10 Countries with the Best Tourism in the Travel & Tourism Development Index - Haurani Ulfa; Fauziah Eddyono (Jurnal Indonesia Sosial Teknologi, 2024)
Good tourism management will improve the welfare of the community in the tourism destination area. The relationship between the competitiveness of tourist destinations will have an impact on sustainable tourism. The purpose of creating competitiveness is to gain and expand market share, both domestic and international, by participating in ensuring that the availability of resources to support tourism is used efficiently and sustainably. Along with the demands of sustainable tourism competitiveness, especially in ASEAN countries, it shows that competitiveness and sustainability have a mutual and supportive relationship. Therefore, a DMO (Destination Management Organization) institution is needed that has the function of leading and coordinating destination elements (attractions, amenities, accessibility) and a sustainable environment.